2018
DOI: 10.18632/oncotarget.24500
|View full text |Cite
|
Sign up to set email alerts
|

Increased visceral fat volume raises the risk for recurrence of hepatocellular carcinoma after curative treatment

Abstract: Obesity is a risk factor for the development of hepatocellular carcinoma (HCC). This study aimed to assess the influence of visceral fat on the recurrence of HCC after curative treatment. In 207 curative cases of HCC, the cross-sectional areas of visceral and subcutaneous fat mass on the computed tomographic image at the fourth lumbar vertebra were normalized by the square of the height to obtain the visceral fat mass index (VFMI) and the subcutaneous fat mass index (SFMI), respectively. Whether VFMI and SFMI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
3
12
0
Order By: Relevance
“…However, in addition to malnutrition, overnutrition must also be avoided, because obesity and related metabolic disorders can promote liver carcinogenesis [ 25 , 26 , 27 ]. A recent study revealed that patients with higher than 47.2 cm 2 /m 2 of VATI had a significantly higher risk of recurrence of HCC after curative treatment [ 28 ]. Sarcopenia, which was defined as an SMI value ≤38.0 cm 2 /m 2 for women and ≤42.0 cm 2 /m 2 for men in Japan [ 29 ], is also a significant prognostic factor of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…However, in addition to malnutrition, overnutrition must also be avoided, because obesity and related metabolic disorders can promote liver carcinogenesis [ 25 , 26 , 27 ]. A recent study revealed that patients with higher than 47.2 cm 2 /m 2 of VATI had a significantly higher risk of recurrence of HCC after curative treatment [ 28 ]. Sarcopenia, which was defined as an SMI value ≤38.0 cm 2 /m 2 for women and ≤42.0 cm 2 /m 2 for men in Japan [ 29 ], is also a significant prognostic factor of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant relationship between the risk of HCC recurrence after curative treatment and various obesity-related disorders such as insulin resistance, oxidative stress, and hyperleptinemia [34,35,36,37]. Excessive accumulation of VFM, which is associated with hepatic inflammation [38], is an independent risk factor for HCC recurrence after curative treatment [39]. Therefore, maintaining the ideal body composition including both skeletal muscle mass and fat mass is required for patients with chronic liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the established risk factors such as HBV, HCV, and alcohol consumption, several components of the metabolic syndrome have been reported to be involved in the increased risk of HCC [7]. We have previously demonstrated that increases in the serum levels of leptin and oxidative stress and increased visceral fat accumulation, all of which are involved in obesity, predict the recurrence of HCC after curative treatment [8,9,10]. Among lifestyle-related diseases, diabetes mellitus (DM) is most deeply involved in liver carcinogenesis [7,11,12,13].…”
Section: Introductionmentioning
confidence: 99%